Paremiološko gradivo iz Zgornjega Posočja v dveh rokopisnih zbirkah. Elementi lokalnosti s poudarkom na kulturnospecifičnih folklornih obrazcih z lokalnimi antroponimi - Ivančič Kutin, Barbara (Slavistična revija, 2022)
The article first briefly presentats two manuscript collections of folklore material from the Upper Posočje region, with an emphasis on paremiological units such as proverbs, comparative folklore forms, and other phrasal constants. Locality is most often expressed by (micro)toponyms and anthroponyms, which, due to the specific cultural context, can only be understood by speakers of the local dialect or local inhabitants. In particular, anthroponyms, such as the official names of residents or their collective nicknames, and of individuals, are associated in this material with folklore narratives and other forms of cultural memory, but their use declines with the passage of time and they are on their way to oblivion, even though they were (for a period of time) part of the conceptual linguistic system.
Keywords: Bovec dialect; bovško narečje; collective nicknames; culturally specific paremia; Dolenc, Janez; kolektivni vzdevki; kratki folklorni obrazci; kulturnospecifične paremije; linguoculturology; lingvokulturologija; short folklore forms